2022
DOI: 10.1002/path.5843
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol promotes cell survival and induces Greb1 expression in granulosa cell tumors of the ovary through an ERα‐dependent mechanism

Abstract: Granulosa cell tumor (GCT) is a form of ovarian tumor characterized by its tendency to recur years after surgical ablation. Little is known about the mechanisms involved in GCT development and progression. GCTs can produce estradiol (E2), but whether this hormone could play a role in this cancer through its nuclear receptors, i.e. ERα and ERβ, remains unknown. Here, we addressed this issue by cell-based and molecular studies on human GCTs and GCT cell lines. Importantly, we observed that E2 significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…In this context wherein ER signaling is inactive, we observed that E2 decreases KGN cell migration through GPER1-mediated ERK1/2 inactivation, therefore possibly preventing GCT metastasis spreading [ 135 ]. Two studies, including ours in a mouse GCT cell line wherein ER signaling is active, support the idea that E2 favors the growth of GCT by promoting cell survival [ 136 , 142 ]. This E2-mediated effect may be triggered by ERα, acting either alone or in combination with ERβ [ 142 ].…”
Section: Roles Of Estrogen In Gctmentioning
confidence: 69%
See 4 more Smart Citations
“…In this context wherein ER signaling is inactive, we observed that E2 decreases KGN cell migration through GPER1-mediated ERK1/2 inactivation, therefore possibly preventing GCT metastasis spreading [ 135 ]. Two studies, including ours in a mouse GCT cell line wherein ER signaling is active, support the idea that E2 favors the growth of GCT by promoting cell survival [ 136 , 142 ]. This E2-mediated effect may be triggered by ERα, acting either alone or in combination with ERβ [ 142 ].…”
Section: Roles Of Estrogen In Gctmentioning
confidence: 69%
“…Two studies, including ours in a mouse GCT cell line wherein ER signaling is active, support the idea that E2 favors the growth of GCT by promoting cell survival [ 136 , 142 ]. This E2-mediated effect may be triggered by ERα, acting either alone or in combination with ERβ [ 142 ]. The ERα-dependency for the pro-survival action of E2 in GCT may explain the relatively limited clinical benefits of aromatase inhibitors, since not all GCT express ERα [ 31 , 136 , 139 , 140 , 141 , 142 ].…”
Section: Roles Of Estrogen In Gctmentioning
confidence: 69%
See 3 more Smart Citations